2018
DOI: 10.3390/insects9020057
|View full text |Cite
|
Sign up to set email alerts
|

Species Composition, Abundance and Seasonal Phenology of Social Wasps (Hymenoptera: Vespidae) in Wisconsin Vineyards

Abstract: Social wasps can be serious pests in fruit growing plantings and are becoming increasingly problematic for grape growers. In this study, we conducted two experiments to assess the species composition and seasonal phenology of social wasps in Wisconsin vineyards in 2015 and 2017. In 2015, three attractants were used: (1) wine; (2) heptyl butyrate (HB); and (3) acetic acid and isobutanol (AAIB) and in 2017, two attractants were used: HB and AAIB. In both years, the same eight species were trapped from the genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…While both ourselves and previous researchers (Tautz & Rostás, 2008) found that “domesticated” S. exigua still responded to auditory predator cues, the effect of this stimulus on “wild” Spodoptera might be substantially greater. Finally, the abundance of social wasps generally increases throughout the summer before peaking in the fall (Guedot et al, 2018; Southon et al, 2019); future work might compare the antipredator responses of spring‐feeding caterpillars with those of summer‐/fall‐feeding species.…”
Section: Discussionmentioning
confidence: 99%
“…While both ourselves and previous researchers (Tautz & Rostás, 2008) found that “domesticated” S. exigua still responded to auditory predator cues, the effect of this stimulus on “wild” Spodoptera might be substantially greater. Finally, the abundance of social wasps generally increases throughout the summer before peaking in the fall (Guedot et al, 2018; Southon et al, 2019); future work might compare the antipredator responses of spring‐feeding caterpillars with those of summer‐/fall‐feeding species.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical attractants were used at each site to thoroughly sample yellowjacket diversity (De Souza et al, 2011). Extensive research involving the effectiveness of chemical attractants for capturing wasp species has concluded that a variety of baits or lures is necessary to sample yellowjacket diversity (Guédot et al, 2018;Landolt & Zhang, 2016;Landolt et al, 2003). Heptyl butyrate (HB) and acetic acid plus isobutanol (AAIB) were used as lures at each site.…”
Section: Sampling Designmentioning
confidence: 99%